Work-Family Conflict Reviewed of Workload and Burnout among Female Employees at Bank X - Rani, Muthya Sri; Kurniawan, Harri; Mariana, Rina (Psyche 165 Journal, 2025)
Career woman is working women​ or do planned activities​ For get results in the form of money or services . Involvement and commitment time women in a family based on not quite enough answer to task House stairs , including look after husband and children make the women Work more often experience conflict . characteristics work of a nature more formal and managerial such as relatively long working hours long and abundant work​ more tend bring up work-family conflict in women work . Load factor overwork​​ have effect double the burden on work-family conflict , in other words high work​ will increase working hours and also cause feelings of tension and fatigue in individuals . When difficulties arise in balance role double result in somebody lost source power that will trigger occurrence burnout. Research objectives This is For know Connection burden work and burnout with work-family conflict in employees Bank X woman. Measuring instruments used in study This is scale work-family conflict, scale burden work and scale burnout . Decision-making techniques sample is purposive sampling , namely technique determination sample with consideration certain . So that amount samples in research This that is as many as 118 people. Based on data analysis , obtained mark correlation multiple of 0.582 with level significance of 0.000 which means hypothesis accepted . This is show that There is significant relationship​ between burden work and burnout with work-family conflict in employees Bank X woman. With big donation effective from variables burden work and burnout with work-family conflict in employees Bank X women amounted to 33.87%.